Anti-Zionism, Anti-Semitism and the Jewish Community in Egypt, 1939 to the Present - Beinin, Joel (Hagar: Studies in Society and Culture, 2002)
The Jews of 20th century Egypt were mostly not Zionists and anti-Semitism did not become a significant factor in modern Egypt until the late 1930s. After the 1948 Arab-Israeli war, under both the monarchy and the regime of the Free Officers, there was a movement towards renormalization of the status of Egyptian Jews. However, the political orientation of the Free Officers tended to exclude Jews from the political community. AntiSemitism in Egypt grew dramatically after the 1979 Egyptian- Israeli peace treaty due to disappointment with Israel’s treatment of the Palestinians and its other actions in the Arab world.